Sistem Informasi Transparansi Pengelolaan Dana Desa: Studi Kasus Kampung Malasaum Distrik Aimas Kabupaten Sorong - Rupilele, Frits G. J.; Lahallo, Fensca F (Universitas Multi Data Palembang, 2024)
Village funds are funds given by the central government to village governments, including Malasaum Village, Aimas District, Sorong Regency to improve village development. However, the management of village funds is often not done properly and transparently. The management and reporting of village funds in Malasaum Village is currently still done manually. In addition, there is no village fund management information system so it is important to design this information system to facilitate reporting, evaluation and control of village fund management and transparency to the community. The design of the Information System carried out in this study uses the Rapid Application Development (RAD) method. This method is an object-oriented approach to software development that aims to shorten the time usually required in the traditional system development life cycle between design and implementation of information systems. As for the design of the system model, it uses unified modeling language (UML) diagrams which include use case diagrams, and activity diagrams. The result of this research is a web-based information system that provides a transparency system for the management of village funds to the community and village officials, among others, this system helps effective reporting management, namely producing reports quickly, accurately and easily understood and efficiency in automating the process of data processing or recording daily transactions and can generate reports quickly and automatically, without requiring a long time.